2011
DOI: 10.1007/s00425-011-1386-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel rice calmodulin-like gene, OsMSR2, enhances drought and salt tolerance and increases ABA sensitivity in Arabidopsis

Abstract: Many abiotic stimuli, such as drought and salt stresses, elicit changes in intracellular calcium levels that serve to convey information and activate adaptive responses. Ca²⁺ signals are perceived by different Ca²⁺ sensors, and calmodulin (CaM) is one of the best-characterized Ca²⁺ sensors in eukaryotes. Calmodulin-like (CML) proteins also exist in plants, but their functions at the physiological and molecular levels are largely unknown. In this report, we present data on OsMSR2 (Oryza sativa L. Multi-Stress-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(126 citation statements)
references
References 48 publications
6
113
0
2
Order By: Relevance
“…In Arabidopsis there are three additional genes associated with the rgsCaM-like clade (CML37, CML39, and CML41). Previous work shows that these Arabidopsis proteins, as well as orthologs in rice (Oryza sativa), are also regulated by abiotic stresses (Vanderbeld and Snedden, 2007;Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis there are three additional genes associated with the rgsCaM-like clade (CML37, CML39, and CML41). Previous work shows that these Arabidopsis proteins, as well as orthologs in rice (Oryza sativa), are also regulated by abiotic stresses (Vanderbeld and Snedden, 2007;Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, local adaptation to coastal, potentially saline impacted environments has been shown before, where a sodium transporter allele conferred elevated salinity tolerance (Baxter et al, 2010). Since calcium sensing is a crucial pathway for salt stress tolerance in Arabidopsis (Guan et al, 2013), and has shown to be important for salt and drought stress in rice (Oryza sativa) (Xu et al, 2011), natural allelic variation at the CaS gene locus might be one way in which coastal populations adapt their growth to a saline environment. As such, our findings provide an excellent starting point to study the links between calcium signaling-dependent root growth and adaptation to growth in saline environments.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of specific stress-responsive genes has been demonstrated to be calciumregulated, for example, in response to cold (Knight et al, 1996;Knight et al, 1997;Tä htiharju et al, 1997;Galon et al, 2010a). The protein intermediates brokering calcium signals to regulate gene expression have also, in some cases, been identified, for example calmodulins (CaMs) (Takahashi et al, 2011), CaM-like proteins (Chiasson et al, 2005;Magnan et al, 2008;Xu et al, 2011), calcium-dependent protein kinases (CPKs) (Boudsocq et al, 2010;Coca and Segundo, 2010), CIPK/CBLs (Albrecht et al, 2003;Weinl and Kudla, 2009), and even transcription factors, such as CaM-binding transcription activators (CAMTAs) (Galon et al, 2008;Doherty et al, 2009;Du et al, 2009;Galon et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%